2017
DOI: 10.1016/j.puhe.2017.01.016
|View full text |Cite
|
Sign up to set email alerts
|

Associations between singing to babies and symptoms of postnatal depression, wellbeing, self-esteem and mother-infant bond

Abstract: Introduction: There is growing research documenting the psychological benefits of singing. However, it remains unknown whether singing to new babies is associated with enhanced maternal mental health. This study had two aims: (i) to explore whether these associations exist, and (ii) to compare the effects of singing to babies with listening to music in order to explore whether the sound of music alone or the physical act of singing might be responsible for effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(36 citation statements)
references
References 12 publications
7
29
0
Order By: Relevance
“…At the same time, playful ID singing can be used to activate and engage the infant in interactive games (Rock et al, 1999; Cirelli et al, 2019). Overall, engagement and connectedness within musical experiences may facilitate social connections between infants and their parents (Fancourt and Perkins, 2017; Cirelli et al, 2018). Thus, we propose that there is another potential function of ID signing, namely, to establish interpersonal synchrony.…”
Section: Rhythms Of Early Interactionsmentioning
confidence: 99%
“…At the same time, playful ID singing can be used to activate and engage the infant in interactive games (Rock et al, 1999; Cirelli et al, 2019). Overall, engagement and connectedness within musical experiences may facilitate social connections between infants and their parents (Fancourt and Perkins, 2017; Cirelli et al, 2018). Thus, we propose that there is another potential function of ID signing, namely, to establish interpersonal synchrony.…”
Section: Rhythms Of Early Interactionsmentioning
confidence: 99%
“…And a further study has found cross-sectional associations between listening to music and depression and well-being among new mothers, with more frequent listening associated with better mental health. 31 However, this study did not look longitudinally nor involved pregnant women.…”
Section: Introductionmentioning
confidence: 98%
“…This may reflect the increased time parents were spending with their child due to Covid-19, the importance of parents in supporting children's social-emotional needs, and/or the general centrality of the parent-child relationship for parents of young children (Borkowski et al, 2001). Music has been linked to several positive psychosocial outcomes in regard to emotions, relationships, and mood including for parents of young children (Croom, 2015;Custodero et al, 2003;Fancourt & Perkins, 2017;Hargreaves & North, 1999). Our results indicate that during a global pandemic, music continues to serve as a social and emotional tool for parents and children.…”
Section: Discussionmentioning
confidence: 69%